TEACHING AND LEARNING ENGLISH FOR INTERNACIONAL RELATIONS: CHALLENGES AND PERSPECTIVES: ENSINAR E APRENDER INGLÊS PARA RELAÇÕES INTERNACIONAIS: DESAFIOS E PERSPECTIVAS - Pacheco, Aline; Boemeke, Amália; Pedron , Laura (Revista CBTecLE, 2022)
Internationalization as a phenomenon or activity naturally entangles the use of multiple languages and or a language as a lingua franca. This is why the teaching and learning of languages for this specific purpose needs to be reflected upon and discussed. This article aims to contribute to these reflections and discussions as it approaches some theoretical conceptions on Internationalization, Intercultural Communication and English for Specific Purposes. In order to verify the application of those concepts, a tentative survey was conducted through a questionnaire answered by undergraduate students of the International Relations Program in the Pontifical Catholic University of Rio Grande do Sul. The answers reinforce the need of a mindful attitude towards teaching and learning English for International Relation Purposes as communication seems to play a crucial role in Internationalization.